2001
DOI: 10.1002/j.1556-6978.2001.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Process Versus Content: Integrating Personal Awareness and Counseling Skills to Meet the Multicultural Challenge of the Twenty‐First Century

Abstract: The authors describe a study in which there was a strong relationship between personal awareness and multicultural counseling skills during group supervision. The authors suggest that during supervision, supervisors should help counselors‐in‐training to attain wisdom, as defined by F. J. Hanna, F. Bemak, and R. C. Chung (1999). This should be done by promoting personal awareness and may result in improvement in both multicultural and general counseling skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…This corroborates findings of an earlier study in which Cronbach's alpha coefficient was .95 (Torres-Rivera et al, 2001). Torres-Rivera et al (2002) did not report internal consistency reliabilities for the CSPD-RF factors.…”
Section: Instrumentssupporting
confidence: 94%
“…This corroborates findings of an earlier study in which Cronbach's alpha coefficient was .95 (Torres-Rivera et al, 2001). Torres-Rivera et al (2002) did not report internal consistency reliabilities for the CSPD-RF factors.…”
Section: Instrumentssupporting
confidence: 94%
“…It is critical that practitioners, administrators, and educators facilitate multicultural skill building and increase their overall knowledge base (Butler, 2003). If the helping profession is to become more multiculturally competent, there must be a stronger emphasis placed on institutional and organizational change in the direction cited above (Butler, 2003).In a study done by Torres-Rivera, Phan, Maddux, Wilbur, and Garrett (2001), they found that many counselor educators who left their training sessions often did not have the knowledge and skill to work effectively with their multicultural clients. Therefore, once they got out into the counseling workforce, they were unable to relate well to their clients or students because of their lack of understanding and skill in working with multicultural people.…”
Section: Graduate Programs and Facultymentioning
confidence: 99%
“…Over the past two decades, counselling professionals have grappled with theories, techniques, and approaches for providing effective multicultural education and diversity competent clinical service (Constantine 2001;D'Andrea 2004;Han and Vasquez 2000;Torres-Rivera et al 2001). Researchers continue to explore the influence of race, among other cultural variables, on the counselling relationship (Burkard et al 2003;Darnell and Kuperminc 2006;Fisher et al 2001).…”
Section: Introductionmentioning
confidence: 98%